THE MECHANISM OF DESIGNING BASED ON STEAM EDUCATION TECHNOLOGY. DESIGNING THE ACTIVITIES OF BUILDING AND CREATING (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2025)
This article discusses the importance of the project-based approach for preschool children based on STEAM technology, the development of children's logical thinking abilities through STEAM education, ideas for constructive play, design activities, and the advantages of engineering activities for children.